2022
DOI: 10.1136/bmj-2021-069445
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, natural history, and hypothesised mechanisms of myocarditis and pericarditis following covid-19 vaccination: living evidence syntheses and review

Abstract: ObjectivesTo synthesise evidence on incidence rates and risk factors for myocarditis and pericarditis after use of mRNA vaccination against covid-19, clinical presentation, short term and longer term outcomes of cases, and proposed mechanisms.DesignLiving evidence syntheses and review.Data sourcesMedline, Embase, and the Cochrane Library were searched from 6 October 2020 to 10 January 2022; reference lists and grey literature (to 13 January 2021). One reviewer completed screening and another verified 50% of ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 82 publications
2
77
3
3
Order By: Relevance
“…Among multiple side effects of BNT162b2 vaccination, myocarditis in particular has been extensively investigated, yet its exact pathogenesis still remains unknown ( 44 ). Although several case studies have reported clinical changes in BNT162b2-MyoC patients, our understanding of BNT162b2-MyoC is still limited mainly due to scarcity of tissue sampling and lack of empirical evidence ( 45 ). Moreover, based on published literature reviews ( 46 , 47 ), among few empirical studies that were conducted with tissue samples from patients, there hasn’t been research that featured detailed transcriptomic profile of the harvested tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Among multiple side effects of BNT162b2 vaccination, myocarditis in particular has been extensively investigated, yet its exact pathogenesis still remains unknown ( 44 ). Although several case studies have reported clinical changes in BNT162b2-MyoC patients, our understanding of BNT162b2-MyoC is still limited mainly due to scarcity of tissue sampling and lack of empirical evidence ( 45 ). Moreover, based on published literature reviews ( 46 , 47 ), among few empirical studies that were conducted with tissue samples from patients, there hasn’t been research that featured detailed transcriptomic profile of the harvested tissues.…”
Section: Discussionmentioning
confidence: 99%
“…If you haven’t experienced myocarditis or pericarditis after vaccination, you might be reassured by data on its low incidence and its mild and self limiting nature (doi:10.1136/bmj-2021-069445). 18 Even though these risks don’t outweigh the benefits of vaccination (doi:10.1136/bmj.o1554),19 the risks loom larger if you’ve been affected by them.…”
mentioning
confidence: 99%
“…Covid-19 mRNA vaccines have been shown to be associated with a short-term increased risk of myocarditis, with the highest risk observed after the second dose relative to the first. 1 The extent of the risk associated with more distant booster doses is less clear, with reports of a lower incidence relative to the second dose 2 or an increase with sequential doses. 3 Besides, it has been suggested that extending the timing between the first two doses could lower the risk of heart inflammation.…”
Section: Main Textmentioning
confidence: 99%
“…Extending our previous study 1 , we conducted a matched case-control study within the entire French population aged 12 or older, from the beginning of the Covid-19 vaccination campaign in December, 27, 2020 to January, 31, 2022.…”
Section: Supplementary Information For the Manuscript "Risk Of Myocar...mentioning
confidence: 99%